Identification of candidate miRNA biomarkers for facioscapulohumeral muscular dystrophy using DUX4-based mouse models - Andreia M. Nunes; Monique Ramirez; Takako I. Jones; Peter L. Jones (Disease Models & Mechanisms, 2021)
Facioscapulohumeral muscular dystrophy (FSHD) is caused by misexpression of DUX4 in skeletal myocytes. As DUX4 is the key therapeutic target in FSHD, surrogate biomarkers of DUX4 expression in skeletal muscle are critically needed for clinical trials. Although no natural animal models of FSHD exist, transgenic mice with inducible DUX4 expression in skeletal muscles rapidly develop myopathic phenotypes consistent with FSHD. Here, we established a new, more-accurate FSHD-like mouse model based on chronic DUX4 expression in a small fraction of skeletal myonuclei that develops pathology mimicking key aspects of FSHD across its lifespan. Utilizing this new aged mouse model and DUX4-inducible mouse models, we characterized the DUX4-related microRNA signatures in skeletal muscles, which represent potential biomarkers for FSHD. We found increased expression of miR-31-5p and miR-206 in muscles expressing different levels of DUX4 and displaying varying degrees of pathology. Importantly, miR-206 expression is significantly increased in serum samples from FSHD patients compared with healthy controls. Our data support miR-31-5p and miR-206 as new potential regulators of muscle pathology and miR-206 as a potential circulating biomarker for FSHD. This article has an associated First Person interview with the first author of the paper.